The role of organisational culture in the environmental awareness of companies - Ágnes Nemcsicsné Zsóka (Journal for East European Management Studies, 2007)
The objective of the article is to highlight the role of environmental values in corporate pro-environmental behaviour. Among the five components of corporate environmental awareness, environmental values are of special importance, as is illustrated by the organisational culture of a Hungarian company showing consistent pro-environmental behaviour regarding all awareness components except values. Empirical research findings - arrived at with the help of Q-methodology - indicate the need for a stable and unambiguous integration of environmental values into organisational culture in order to achieve consistent pro-environmental behaviour at companies. – – Der Artikel betont die Rolle der Werte im umweltorientierten Organisationsverhalten. Unter den fünf Komponenten des Umweltbewußtseins gewinnen umweltrelevante Werte spezielle Wichtigkeit, was durch die Organisationskultur einer ungarischen Firma illustriert wird. Diese Firma weist ein konsistentes Verhalten in fast allen Komponenten des Umweltbewußtseins auf, nur nicht hinsichtlich der Werte. Empirische Ergebnisse - gewonnen durch Q-Methodologie - deuten darauf hin, daß umweltbezogene Werte in die Organisationskultur auf eine stabile und konsistente Weise integriert werden müssen, um ein richtiges Umweltbewußtsein in Unternehmen erreichen zu können.
Keywords: 650; organisational culture; pro-environmental organisational behaviour; environmental awareness; environmental values; Q-methodology